Phosphonium Modification Leads to Ultrapermeable Antibacterial Polyamide Composite Membranes with Unreduced Thickness. Issue 23 (30th April 2020) - Peng, Huawen; Zhang, Wen‐Hai; Hung, Wei‐Song; Wang, Naixin; Sun, Jian; Lee, Kueir‐Rarn; An, Quan‐Fu; Liu, Cheng‐Mei; Zhao, Qiang
Abstract: Water transport rate in network membranes is inversely correlated to thickness, thus superior permeance is achievable with ultrathin membranes prepared by complicated methods circumventing nanofilm weakness and defects. Conferring ultrahigh permeance to easily prepared thicker membranes remains challenging. Here, a tetrakis(hydroxymethyl) phosphonium chloride (THPC) monomer is discovered that enables straightforward modification of polyamide composite membranes. Water permeance of the modified membrane is ≈6 times improved, give rising to permeability (permeance × thickness) one magnitude higher than state‐of‐the‐art polymer nanofiltration membranes. Meanwhile, the membrane exhibits good rejection ( R Na2SO4 = 98%) and antibacterial properties under crossflow conditions. THPC modification not only improves membrane hydrophilicity, but also creates additional angstrom‐scale channels in polyamide membranes for unimpeded transport of water. This unique mechanism provides a paradigm shift in facile preparation of ultrapermeable membranes with unreduced thickness for clean water and desalination. Abstract : Facile modification of polyamide composite membranes by an inexpensive phosphonium monomer featuring tetrahedral geometry is found to create additional water transport channels, improving the water purification performance without reducing film thickness. Compared with cutting‐edge ultrathin membranes, the modified membrane highlights good rejection, antibacterial properties, superior water permeability, and facile preparation.